2019
DOI: 10.3892/mmr.2019.10612
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin relieves paraquat‑induced lung injury through inhibiting the thioredoxin interacting protein/NLR pyrin domain containing 3‑mediated inflammatory pathway

Abstract: When paraquat (PQ) enters the human body, it increases oxidative stress and inflammation, ultimately resulting in acute lung injury (ali). curcumin, a naturally occurring compound, has been reported to ameliorate PQ-induced ali; however, the underlying molecular mechanisms remain unclear. in the present study, normal lung fibroblasts (WI-38VA13) were treated with 10 µmol/l PQ for 48 h, followed by a further 48 h incubation with 300 µmol/l curcumin. cells were then harvested to determine their viability. Flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Curcumin is able to reverse this effect and enhance the effectiveness of SOD so as to maintain the oxidant/antioxidant balance and mitigate liver damage (Hemeida and Mohafez, 2008). Recently, curcumin was reported to oppose the effect of ROS on pro-inflammatory cytokine expression (e.g., IL-1b, IL-18) by downregulation of the thioredoxin interacting protein/NLR pyrin domain containing 3 (TXNIP/NLRP3) (Ren et al, 2019).…”
Section: Scavenges Rosmentioning
confidence: 99%
“…Curcumin is able to reverse this effect and enhance the effectiveness of SOD so as to maintain the oxidant/antioxidant balance and mitigate liver damage (Hemeida and Mohafez, 2008). Recently, curcumin was reported to oppose the effect of ROS on pro-inflammatory cytokine expression (e.g., IL-1b, IL-18) by downregulation of the thioredoxin interacting protein/NLR pyrin domain containing 3 (TXNIP/NLRP3) (Ren et al, 2019).…”
Section: Scavenges Rosmentioning
confidence: 99%
“…Some studies have shown that PQ-induced cytotoxicity is related to oxidative stress, including excessive production of ROS and lipid peroxidation (Matern et al, 2015;Ren et al, 2019;Schuttler et al, 2019). The main characteristics of oxidative stress are dysfunction of antioxidant system or excessive production of free radicals (El-Boghdady et al, 2017;Guo et al, 2017;Cavaliere et al, 2019;Lopes et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the molecular mechanism of hepatotoxicity induced by PQ is not completely understood. It is known that the redox response is one of the main factors involved in the toxic effects of PQ (Ren et al, 2019). It has been reported that PQ molecules can interfere with the electron transport chain and then inhibit the synthesis of NADPH (Gao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrate that derivatized curcumin molecules were more effective than curcumin alone in lowering TXNIP expression. Other studies have shown the effectiveness of curcumin in vitro and in vivo in inhibiting TXNIP expression but at higher doses than we used for testing the fluorinated curcumin compound [ 163 , 164 ]. The effect of curcumin on TXNIP expression appears to be through the activation of AMPK [ 81 , 165 ].…”
Section: Modulating Txnip Expressionmentioning
confidence: 99%